Recommendations of The Ombudsman’s Dilemma: Between Law Enforcement Officials and Protection of Credibility - Dewi, Dyah Adriantini Sintha (International Conference of Moslem Society, 2018)
The Ombudsman as an external oversight body for official performance, in Fikih Siyasah (constitutionality in Islam) is included in the supervision stipulated in legislation (al-musahabah al-qomariyah). Supervision is done so that public service delivery to the community is in accordance with the rights of the community. This is done because in carrying out its duties, officials are very likely to conduct mal administration, which is bad public services that cause harm to the community. The Ombudsman is an institution authorized to resolve the mal administration issue, in which one of its products is by issuing a recommendation. Although Law No. 37 of 2018 on the Ombudsman of the Republic of Indonesia states that the recommendation is mandatory, theombudsman's recommendations have not been implemented. This is due to differences in point of view, ie on the one hand in the context of law enforcement, but on the other hand the implementation of the recommendation is considered as a means of opening the disgrace of officials. Recommendations are the last alternative of Ombudsman's efforts to resolve the mal administration case, given that a win-win solution is the goal, then mediation becomes the main effort. This is in accordance with the condition of the Muslim majority of Indonesian nation and prioritizes deliberation in resolving dispute. Therefore, it is necessary to educate the community and officials related to the implementation of the Ombudsman's recommendations in order to provide good public services for the community, which is the obligation of the government.